Implementasi Prinsip Good Governance Melalui Pelatihan dan Pendampingan Peningkatan Capacity Building Pada Pengelolaan BUMDes Kecamatan Gumukmas Kabupaten Jember - Zainuri, Zainuri; Fathorrazi, Moehammad; Wahyu Prianto, Fajar (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
This paper aims to provide an overview of the topic at hand. It explores various aspects, and The Village-Owned Enterprises (BUMDes) play a crucial role in the economic success of rural areas. The village government manages the Village-Owned Enterprises (BUMDes) and possesses legitimate legal status. The establishment process of BUMDes is regulated under the Village Regulation, with the management comprising representatives from the village government and residents. The BUMDes is not just a commercial institution but also a social institution. BUMDes implement good governance to fulfill both roles by adhering to cooperativeness, participation, emancipation, transparency, accountability, and sustainability principles. The mechanisms of a professional and self-reliant member base and self-help are key to its success. This article reflects the training experiences experienced by the administrators of Village-Owned Enterprises (BUMDes) located in the villages of Gumukmas District, Jember Regency. The training session elicited enthusiasm from the participants, who eagerly posed questions and discussed their challenges in managing capital in BUMDes. After the training ends, participants gain relevant knowledge regarding analytical and careful management skills of Village-Owned Enterprises (BUMDes), which is the aim of this training.This study focuses on the role of BUMDes (Village-Owned Enterprises) in promoting good governance and capacity building through training initiatives.